MARRIAGE LAW IN INDONESIA (A Study of Law Number 1 of 1974 concerning Marriage, a Compilation of Islamic Law, and a Gender-Based Research Review) - Lenny Guspidawati; Sofia; Nur Nasrina; Suja'i Sarifandi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study examines the construction of marriage law in Indonesia through a comparative analysis of Law Number 1 of 1974 and the Compilation of Islamic Law (KHI). The main focus of the research is to evaluate the relevance of these legal products to the principles of gender equality and justice. Using a literature review method and critical analysis of various previous research, this study found tensions between positive legal norms, classical fiqh doctrine, and the dynamics of women's human rights in Indonesia. The results of the study indicate that although reforms have been carried out, several articles still retain gender bias that has the potential to discriminate against women's rights. Therefore, a reorientation of family law that is more inclusive and gender-responsive is needed. Marriage Law in Indonesia as regulated in Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI) aims to create a harmonious family, but still contains patriarchal nuances that place the husband as the head of the family and the wife as the housewife, thus triggering the need for a reinterpretation or reformulation of the law that is more gender-oriented and equal. This is considering that: (1) Law Number 1 of 1974 concerning Marriage adheres to the principle of open monogamy and requires marriage registration for formal legality, (2) there is still gender inequality in the articles that regulate the roles of husband and wife (Article 31 of Law Number 1 of 1974 concerning Marriage), which often limits the wife's public space, (3) gender-perspective research encourages the reconstruction of marriage law to be more egalitarian, non-discriminatory, and in accordance with modernity and equal rights between husband and wife, and (4) Law Number 1 of 1974 concerning Marriage does not accommodate interfaith marriages, affirming the validity of marriage according to the laws of each religion.